A new analytical concept based on chemistry and toxicology for herbal extracts analysis: From phenolic composition to bioactivity. (June 2020) - Santos, Jânio Sousa; Escher, Graziela Bragueto; Vieira do Carmo, Mariana; Azevedo, Luciana; Boscacci Marques, Mariza; Daguer, Heitor; Molognoni, Luciano; Inés Genovese, Maria; Wen, Mingchun; Zhang, Liang; Oh, Won Young; Shahidi, Fereidoon; et al.
Graphical abstract: Highlights: Fermented rooibos, roasted mate, and white tea extracts were combined at an optimized formulation. The optimized extract presented the most varied phenolic composition. DNA and LDL oxidation was decreased when pretreated with the optimized extract. The chlorogenic acid content was related to decreased lipoperoxidation of Wistar rat brain homogenate. Abstract: Studies regarding the bioactivity of teas are mainly based on the phenolic composition and in vitro antioxidant activity of the herbal species used in their preparation. The aim of this study was to compare the in vitro and ex vivo antioxidant activity, cytotoxic/antiproliferative activity against cancer cells, the inhibitory activity of α-amylase, α-glucosidase and angiotensin I-converting enzymes, as well as the inhibition of DNA-induced fission of the peroxyl radical, in relation to aqueous extracts of Camellia sinensis var. sinensis (CS), Ilex paraguariensis (IP), Aspalathus linearis (AL) and an optimised extract (OT) containing the three herb species. A bivariate and multivariate statistical approach was employed to associate functional activities with individual phenolic composition. The CS and OT extracts showed the highest levels of hesperidin, quercetin-3-rutinoside, (-)-epigallocatechin-3-gallate and isoquercitrin. The CS and OT extracts showed the highest antioxidant activity, greater ability to inhibit α-amylase and proliferation of HCT8 cells, and greater ability to reduce Folin-Ciocalteu reagent. The AL extract, which is the major source of quercetin-3-rutinoside, hesperidin and isoquercitrin, showed the highest ability to inhibit α-glucosidase, the inhibition of LDL oxidation and protection of human erythrocytes. The IP extract showed the highest inhibition of lipoperoxidation in brain homogenate of Wistar rats, antihypertensive activity, and A549 cell proliferation; chlorogenic acid was its major phenolic compound. In general, the in vitro functionality of each extract was dependent on its chemical composition and the OT extract presented the most varied phenolic composition, and biological activity similar to the CS sample. In conclusion, the mixture of CS, AL, and IP represents a chemical and functional-based strategy to develop functional teas.